E-commerce adoption by Indonesian small agribusiness: reconsidering the innovation-decision process model - Kartiwi, Mira; Machfud, Alfi Khairiansyah (2013)
Granted that studies on e-commerce adoption by small business in developing countries has received a significant attention in the past decade, most of the studies recorded in the literature were mainly focused on manufacturing, distribution and service sector. Limited attention had been given to agribusiness sector despite its significance to the economy. Many studies have adopted Rogers innovation-decision process model to analyse the adoption process. However, only a portion of the model were used in those studies. This paper discusses and proposes Rogers model incorporating all elements of the innovation decision process model including the stages of innovation decision and its influencing factors such as prior conditions, communication channels, characteristics of the adopter, and the perceived characteristics of e-commerce; to gain a better understanding on e-commerce adoption process. This paper spotlights Indonesian small agribusiness whereby e-commerce adoption studies still scarce.